Some determinants of intermediate local governments' spending efficiency: The case of French départements - Maria Nieswand; Stefan Seifert (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Efforts undertaken by France to restructure the allocation of governmental competencies increased the importance of subnational governments by transferring additional tasks. This paper analyzes the efficiency of public spending on an intermediate government level for a sample of 96 départements in metropolitan France in 2008. Spending efficiency is measured using Data Envelopment Analysis (DEA). Results indicate significant room for improvements and detect spending inefficiencies averaging between 10 and 22 percent, depending on model specification. To explain efficiency, a bootstrapped truncated regression, following Simar and Wilson (2007), is applied. The second-stage regression shows that efficiency is also determined by exogenous factors and identifies the distance to the national capital, inhabitants' income and the share of inhabitants of an age over 65 as significant determinants of efficiency.
Keywords: C14; H11; H72; 330; intermediate government spending efficiency; nonparametric efficiency analysis; bootstrapped truncated regression; Öffentliche Ausgaben; Provinz; Technische Effizienz; Data-Envelopment-Analyse; Schätzung; Frankreich